2017
DOI: 10.2298/tsci140814087b
|View full text |Cite
|
Sign up to set email alerts
|

A comparative experimental study on engine operating on premixed charge compression ignition and compression ignition mode

Abstract: New combustion concepts have been recently developed with the purpose to tackle the problem of high emissions level of traditional direct injection Diesel engines. A good example is the premixed charge compression ignition combustion. A strategy in which early injection is used causing a burning process in which the fuel burns in the premixed condition. In compression ignition engines, soot (particulate matter) and NO x emissions are an extremely unsolved issue. Premixed charge compression ignition is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Relatively promising lower percentage increments of 27.49% and 33.18% in HC and CO results respectively were found in comparison to the average previous studies on PCCI combustion. Minimized HC and CO percentage increments are promising results comparing with most previous studies having more than 30% increments even more than 100% increments [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 91%
“…Relatively promising lower percentage increments of 27.49% and 33.18% in HC and CO results respectively were found in comparison to the average previous studies on PCCI combustion. Minimized HC and CO percentage increments are promising results comparing with most previous studies having more than 30% increments even more than 100% increments [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 91%
“…From other research on PCCI operation, 25 °BTDC of injection timing and IMEP of 287 kPa was found best due to the reasons: lower NOx production of 3.1 g/kWh and lower CO and HC including lower smoke emissions [5]. Studies revealed that HC and CO emissions were found out 30 times greater in the PCCI type of combustion compared with the conventional CI mode of combustion [6,7].…”
Section: Introductionmentioning
confidence: 99%